The Influence of Investment Knowledge on Investment Interest With Celebrity Endorser Moderation In FEB UKSW Students - Valvio Elroi Wahani; Harijono Harijono (Journal Research of Social Science, Economics, and Management, 2022)
Investment knowledge is felt to be able to make students interested in buying company shares and external encouragement is allegedly able to reduce investment interest, such as endorser intervention, making investors not interested in investing in company shares. The purpose of this study is to test that celebrity endorsers can weaken the relationship between knowledge of stock investment and interest in investing in stocks. This research is included in quantitative research with primary data obtained through online questionnaires. The survey was conducted with 100 selected respondents from students or alumni of the Satya Wacana Christian University Faculty of Economics and Business. The results of the study prove that investment knowledge has a positive effect on investment interest. Meanwhile, celebrity endorsers can weaken the influence of investment knowledge on investment interest.